A survey of post anesthetic pain management in Thailand - Somrat Charuluxananan (2018)
Objectives: The Royal College of Anesthesiologists of Thailand aimed to study status of post anesthetic pain management to determine factors for quality improvement of anesthesia services in Thailand. Material and Method: A pre-planned structured questionnaire regarding demographic variables, early and late postoperative pain management, establishment of the post anesthesia care unit (PACU) was requested to be filled in by nurse anesthetists attending the refresher course lectures of the Royal College of Anesthesiologists of Thailand in August 2007. Results: Of 280 questionnaires, 261 respondents (93%) returned the questionnaires. Most of the respondents (94%) worked in government hospitals. One-third practiced in hospitals without an anesthesiologist. Twenty percent of respondents reported absence of PACU in their hospitals. Anesthesia personnel took responsibility of and prescribed pain medication in the PACU in 69% and 55% respectively. Intravenous route was the most frequent mode of pain medication administered. Percentages of respondents who reported no post anesthetic pain management guidelines and no record of pain assessment in PACU were 39% and 49% respectively. At the surgical ward, surgeons played major roles for postoperative management (91%) and intramuscular injection was the most preferable route. Seventy-one percent of respondents reported no record of pain assessment. Conclusion: Post anesthetic pain management continues to be undermanaged. Establishment of PACU, increasing the number of anesthesia personnel including MD anesthesiologists, providing clinical guidance for post anesthetic pain management are suggested corrective strategies. Establishment of acute pain service in big hospitals should be promoted.